DOP32 Crohn's disease stricture matrisome analysis reveals the anti-fibrotic activity of milk-fat globule-epidermal growth factor 8 (MFGE8). (30th January 2023) - Lin, S; Wang, J; Mukherjee, P; Mao, R; West, G; Czarnecki, D; Zhao, S; Elias, M; Nguyen, Q T; Chandra, J; Le, T H N; Chen, M H; et al.
Abstract: Background: Intestinal fibrosis is considered an inevitable consequence of chronic inflammatory bowel disease (IBD), leading to stricture formation and need for surgery. During the process of fibrogenesis, extracellular matrix (ECM) components critically regulate the function of mesenchymal cells. We characterized the composition and function of the ECM in fibrostenosing Crohn's disease (CD) and control tissues. Methods: Decellularized full thickness intestinal tissue platforms were tested using three different protocols and ECM composition in different tissue phenotypes was explored by proteomics and validated by quantitative polymerase chain reaction (qPCR) and immunohistochemistry. Primary human intestinal myofibroblasts (HIMF) treated with Milk Fat Globule-Epidermal growth factor 8 (MFGE8) were evaluated regarding mechanism of their anti-fibrotic response, and the action of MFGE8 was tested in experimental intestinal fibrosis. Results: We established and validated an optimal decellularization protocol for intestinal IBD tissues. Matrisome analysis revealed elevated MFGE8 expression in CD strictured tissue (CDs), which was confirmed at the mRNA and protein levels. Treatment with MFGE8 inhibited ECM production in normal control (NL) HIMF but not CDs HIMF. Next generation sequencing (NGS) uncovered functionally relevant integrin-mediated signaling pathways, and blockade of integrin αvβ5 and focal adhesion kinase rendered HIMF non-responsive to MFGE8. MFGE8 prevented and reversed experimental intestinal fibrosis in vitro and in vivo . Conclusion: MFGE8 displays anti-fibrotic effects, and its administration may represent a future therapeutic approach for prevention of IBD-induced intestinal strictures.